Nonsense-associated altered splicing of MAP3K1 in two siblings with 46,XY disorders of sex development - Igarashi, Maki (Sci Rep, 2020)
Although splicing errors due to single nucleotide variants represent a common cause of monogenic disorders, only a few variants have been shown to create new splice sites in exons. Here, we report an MAP3K1 splice variant identified in two siblings with 46,XY disorder of sex development. The patients carried a maternally derived c.2254C>T variant. The variant was initially recognized as a nonsense substitution leading to nonsense-mediated mRNA decay (p.Gln752Ter); however, RT-PCR for lymphoblastoid cell lines showed that this variant created a new splice donor site and caused 39 amino acid deletion (p.Gln752_Arg790del). All transcripts from the variant allele appeared to undergo altered splicing. The two patients exhibited undermasculinized genitalia with and without hypergonadotropism. Testosterone enanthate injections and dihydrotestosterone ointment applications yielded only slight increase in their penile length. Dihydrotestosterone-induced APOD transactivation was less significant in patients’ genital skin fibroblasts compared with that in control samples. This study provides an example of nonsense-associated altered splicing, in which a highly potent exonic splice site was created. Furthermore, our data, in conjunction with the previous data indicating the association between MAP3K1 and androgen receptor signaling, imply that the combination of testicular dysgenesis and androgen insensitivity may be a unique phenotype of MAP3K1 abnormalities.